THE GENETIC STRUCTURE OF THEWHITE CYPRINID (TOR TAMBROIDES) POPULATIONS BASEDON COIGENE SEQUENCE ANALYZES - Arif Wibowo; Husnah Husnah (Indonesian Fisheries Research Journal, 2012)
The study analyzed nucleotide sequences from the mitochondrial cytochrome oxidase subunit (COI) gene region (654) to investigate the genetic structure of the white cyprinid (Tor tambroides) among nine populations from the Manna and Semanka Rivers. A total of 36 individuals were collected for this work. Five nucleotides were found to be variable, resulting in 4 haplotypes. Among the nine populations of Melebuy in Semanka River represents the highest level of variability (h = 1.000, π = 0.0015) whereas Kerinjing, Merabung and Kotabumi populations represent the highest level of variability in Manna River (h = 0.667, π = 0.0020). The Batu Aji, Air Sebilo and Kutopadang populations exhibit the lowest level of variability (h = 0.000, π = 0.000). There is an integrated population throughout all sample sites in Manna River. However, the AMOVA analysis provided corroborating evidence for genetic structure obtained from Nei’s genetic diversity statistic and the FST value (0.310), suggested there is genetic divergence among populations of those populations. Of the total genetic diversity, 35% was attributable to inter-population diversity and the remainder (68.92%) to differences within populations. These two approaches produced a picture of genetic structure in Manna and Semanka River. A molecular phylogenetic tree constructed using The Neighbor-joining (NJ) method showed the 4 haplotypes were assigned to two clades associated geographic regions. These results provide basic information for the conservation and sustainable exploitation of this species.